Practice for Life: Making Decisions in College: By Lee Cuba, Nancy Jennings, Suzanne Lovett, and Joseph Swingle, 2016. Cambridge, MA: Harvard University Press, 238 pages, ISBN: 978-0674970663, 35.00. Issue 3 (3rd July 2018) - Andersen, Kent
Abstract: Given that the observations in Practice for Life: Making Decisions in College are obvious to most readers, one might easily overlook the book's importance for college student development. Yet, the findings from a longitudinal study of 36 graduates in 2010 from five residential liberal arts colleges in the Northeast provide insight into student choices and thus invite reconsideration of how best to structure student social and academic engagement. This review summarizes the book's major topics and provides additional context for making sense of the findings.